Relationship of information and communication technology (ICT) and stock market development (SMD): Empirical evidence using a panel of ASEAN-6 and East Asian-3 countries - Dela Cruz, Erica Jillian Allison S. (Animo Repository, 2022)
The objective of the study was to analyze the impact of Information Communication Technology (ICT) and select control variables on the Stock Market Development of ASEAN-6 and East Asian-3 countries. The study examined data from the World Bank spanning from the years 2010 to 2019 through a panel data regression which concluded that the OLS Model is more effective than Fixed Effects Model and Random Effects Model. The first model, Stock Market Total Value Traded (SMTV), found that there is a significant relationship between the lagged value of Stock Market Total Value Traded (SMTV_1), Number of Broadband Users (NBU), Number of Mobile Users (NMU), GDP, and EcoStatusDeveloping to Stock Market Total Value Traded (SMTV). The second model, Stock Market Capitalization (SMC), found that there is a significant relationship between the lagged value of Stock Market Capitalization (SMC_1), Number of Fixed Telephone Subscribers (NFTS), Number of Mobile Users (NMU), and GDP to Stock Market Capitalization (SMC). The third model, Stock Market Turnover Ratio (SMTR), found that there is a significant relationship between the Number of Broadband Users (NBU), Internet Users (IU), and Number of Mobile Users (NMU) to Stock Market Turnover Ratio (SMTR). Finally, the fourth model, Number of Listed Companies (NLC), found that there is a significant relationship between Number of Fixed Telephone Subscribers (NFTS), and Number of Broadband Users (NBU) to Number of Listed Companies (NLC). The study concluded that ICT boosts stock market development.